The hermeneutic circle of language and the limits of text - BOULEDJMAR, Fadila (Journal of Human Sciences, 2025)
Since the dawn of creation, the human world has witnessed different perceptions of communication,they used many; verbal and non-verbal means (gestures, images, symbols). To achieve Their goals in the best possible way, So the writing was the most perception used to simulate the life with langage wich is the grate unit in expretion operation,because the,Langage system and its symbols are able to keep the human history in all times,as it published the civelization between humanity and identify it. Consequently,langage become the important prevailing project to this day .therefor Researchers took various ways to stady its knowledges whether who is interested to its advantages or described its negatives to discover the texts’s hidden essence . finally,to approach this last, must be study the relationship between Literary Genres and its critical practices by suggesting the concept of the linguistic circle, thus what is meant by this circle?